PENGARUH EMPLOYEE ENGAGEMENT DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOUR TERHADAP KINERJA ORGANISASI - Cecep Indra Surawijaya; Satiri (Jurnal Satya Mandiri Manajemen dan Bisnis, 2018)
The purpose of this study is to find out the influence of employee engagement and organizational citizenship behavior of non-academic staff toward the organizational performance. The type of research is a quantitative research which using survey method, sample and questioner. The research is conducted in the university of XYZ at the district area of Tangerang by using 89 sample employees of non-academic staff. The result of the study indicates that employee engagement and organizational citizenship behavior of non-academic staff has a significantly influenced to the organizational performance. It can be explained by the comparison of F-distribution showed that F-test value of two independent variables are equal to 43.977 with a significance level of 0% or below 0.05% (5%) which are greater than F-table value that has equal to 3.10. Besides that, the percentage of influence of two independent variables can be determined by the value of the coefficient of determination (R 2) of 50.6%, while 49.9% is influenced by other variables which are not mentioned on this research.